A Quick "Environment Check" for All Ages: Validating the New Age-Inclusive Work Environments Instrument. Issue 7 (27th October 2022) - Owen, Mikaela S; Berthelsen, Hanne; Jamieson, Stephanie D; Westerlund, Hugo
Abstract: Background and Objectives: The global aging workforce necessitates new approaches in designing work environments to cater to the needs of increasingly age-diverse work groups. The Organisation for Economic Co-operation and Development (OECD) has in reaction outlined that organizations need to provide age-inclusive work environments that support the needs of their multigenerational workforce, to ensure their sustainability and profitability. To capture the age inclusiveness of the work environment, the present study proposes and validates an age-inclusive "environment check" for organizations referred to as the Age-Inclusive Work Environment Instrument (AIWEI), which covers discrimination, inclusion, and development opportunities. Research Design and Methods: We validate the 9-item AIWEI using cross-sectional and multilevel data from 2, 892 Swedish workers across 101 workplaces who completed an online survey, using confirmatory factor analyses across young, middle-age, and older workers. Using a nomological approach, we also evaluate the concurrent validity of the AIWEI with a 2-1-1 path analysis. Results: The factor analyses supported a 3-factor model comprising of inclusion, discrimination, and development opportunities, across 3 age groups (i.e., young, middle-age, and older workers). These 3 factors had high Intraclass Coefficient (ICC) scores showing consistency in responding in the workplace. In accordance with the nomological approach, the factors of the AIWEI were linked with Psychosocial Safety Climate, burnout, and engagement, demonstrating concurrent validity for the AIWEI. Discussion and Implications: This new "environment check" provides a way to capture age-inclusive work environments for both younger and older workers, in an age-diverse workforce. In the validation process, age-inclusive work environments were found to exist as a group phenomenon, through shared perceptions within an organization, as well as an individual phenomenon, as experiences specific to an individual. This is important for the development and implementation of policies and strategies designed to benefit workers and organizations.